Street children: “Running from” or “running to”? - Roux, J. le (Koers, 1997)
The street child phenomenon presents a complex issue resulting from a diversity of integrated factors. The problem should therefore preferably be explained and addressed holistically. A search of available literature on street children clearly indicates that street children per se are not the primary problem. The phenomenon o f street children is merely a symptom of a problem underlying the intolerable situation of these children's family and community lives. In this article it is explained that the street child phenomenon is thus symptomatic of contemporary twentieth century conditions. "Running from " and “running to " are in fact intereffective tendencies or reactions to a complicated polarised society: two sides of a common coin.